Lightning induced surges on an unenergized test overhead telecommunication subscriber line - Sorwar, M.G.; Ahmad, Hussein; Ali, M.M.; Ramli, A.; Othman, N.; Yahya, P. (1998)

(untitled)
Voltages induced on a test unenergized 1.8 km straight overhead telecommunication subscriber line by nearby lightning return stroke to ground is presented by solving transmission line coupling equations using time domain approach in combination with the numerical calculation of horizontal and vertical electric fields from return stroke current as inducing source. Both horizontal and vertical electric fields have a significant effect on induced voltages. The effect of the line length and line height on induced voltages is illustrated in this paper. A comparison between numerically calculated data and experimentally recorded data is also made in this paper. The ground conductivity is considered infinite and a triangular current pulse moving from ground to cloud through a 4 km upright vertical channel is taken as channel current. It is found that the calculated results are in reasonably good agreement with experimental results